The influence of the geometric scale model on the physical modelling of the wave propagation and breaking in a flume - Lemos, R. (2009)
This paper describes the set of model scale experiments carried out at the National Civil Engineering Laboratory (LNEC) that aims at simulating, using different model scales, the wave propagation along a constant slope bottom that ends on a sea wall coastal defence structure, a common structure employed in the Portuguese coast. This study focuses especially on the complex physical processes involved in the breaking zone and related to wave-structure interaction (such as wave induced pressures at the structure, run-up levels and wave overtopping). The experiments were performed for different incident wave conditions (regular and irregular) and at several different model scales: 1:10, 1:20, 1:30, 1:40 and 1:60. Measurements of the free surface elevation were made on 26 different locations using wave gauges. Moreover, 30 repetitive tests for a selected wave condition were performed to evaluate the error associated to the signal conversion and its propagation on the calculation of derivative variables. A statistical analysis of the free surface elevation data for the different incident wave conditions for the different model scales with regular and irregular waves is presented. That will permit to evaluate the influence of the geometric scale model and the type of waves (regular or irregular) on the physical model results. Moreover, it was performed a statistical analysis to evaluated the variability of the measurements.